Changing pattern of paediatric inflammatory bowel disease in northern Stockholm 1990–2001. Issue 10 (11th September 2003) - Hildebrand, H; Finkel, Y; Grahnquist, L; Lindholm, J; Ekbom, A; Askling, J
Abstract : Background: An increased incidence of paediatric Crohn's disease was reported recently by our group. Aims: To assess the incidence and characteristics of inflammatory bowel disease (IBD) in northern Stockholm between 1990 and 2001. Methods: All records of individuals 0–15 years of age with suspected IBD in the population based catchment area of 180 000 individuals were scrutinised using defined diagnostic criteria. Patient files were searched for relatives with IBD, and for concomitant autoimmune diseases. Results: A total of 152 children were diagnosed with IBD, corresponding to an overall incidence (per 100 000) of IBD of 7.4. The incidence of Crohn's disease (CD) was 4.9, ulcerative colitis (UC) 2.2, and indeterminate colitis 0.2. Between 1990 and 2001, there was a marked increase in the incidence of CD while the incidence of UC was almost unchanged, leading to a net increase in the overall occurrence of IBD. There was a male dominance of CD. Fourteen per cent and 11% of patients with CD and UC, respectively, had a first or second degree relative with IBD. Eighteen per cent and 10% of patients with CD and UC, respectively, had a concomitant autoimmune disease. Ten patients with CD (10%) underwent surgery. Conclusions: The incidence of CD has increased in northern Stockholm. The current incidence is higher than that reported from other areas. Our results suggest a shift in presentation and diagnosis from UC towards CD, but also a net increase in IBD. Concomitant autoimmune disorders and family history are common in paediatric IBD.